"I'd be sleeping in the park, I reckon": Lived Experience of Using Financial Counselling Services in South Australia*. Issue 4 (7th September 2020) - Pollard, Christina M.; Booth, Sue; Louth, Jonathan; Mackenzie, Catherine; Goodwin‐Smith, Ian
Abstract : The need for non‐profit financial services increases with economic hardship. Consumers' experience of accessing non‐profit financial counselling services in South Australia was explored across five focus groups. Thirty‐six participants discussed service efficiency and potential improvements. The qualitative analysis we completed revealed five themes. Regarding non‐profit financial services: (i) Financial counsellors are life changers ; (ii) Microfinance is "critical for survival"; and (iii) They're "hidden". For‐profit products are (iv) Fast & easy "at a cost"; and there is (v) Frustration with broader system failures . Non‐profit financial services assisted with consumption smoothing and emotional support, but without adequate income financial well‐being was not established. Consumers rely on for‐profit products in crisis situations. Findings support policy to build financial resilience and increase income.